Rizal Halim Adirasyid Evaluasi Usability Situs Web Resmi Pemerintah Kabupaten Sidoarjo Menggunakan Metode Usability Testing dan Evaluasi Heuristic - Rizal Halim Adirasyid; Hanifah Muslimah Az-Zahra; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The website developed by the Regional Government aims to encourage the realization of e-government that is good governance, in accordance with Presidential Instruction No. 3 of 2003. Public information disclosure is important to build good governance, in accordance with Law No. 14 of 2008. The Website of Sidoarjo in sidoarjo.go.id is hoped that the community can access the information of it. In its development, the website still has several shortcomings, so an evaluation is needed to improve its quality. One of them is by evaluating the utility to find out the easiest way of users in using the website and whether the user is satisfied or not with the system. This study uses two methods, namely usability testing, and heuristic evaluation. It is expected that both methods can find out the problems from two different user points of view. The literature that is used in this study is a theory by Jakob Nielsen (1994) which stated that there are 10 general principles in interaction design called heuristic because as a general rule it is not a special rule. The results of usability testing, the effectiveness are 100%, the efficiency of the average time used is 40 seconds, and the average number of clicks is 6 times to complete the task, and user satisfaction from the questionnaire value of 62 includes Grade D or High Marginal which has the quality of